2018
DOI: 10.1074/jbc.ra117.001215
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for disassembly of katanin heterododecamers

Abstract: The reorganization of microtubules in mitosis, meiosis, and development requires the microtubule-severing activity of katanin. Katanin is a heterodimer composed of an TPasessociated with diverse cellular ctivities (AAA) subunit and a regulatory subunit. Microtubule severing requires ATP hydrolysis by katanin's conserved AAA ATPase domains. Whereas other AAA ATPases form stable hexamers, we show that katanin forms only a monomer or dimers of heterodimers in solution. Katanin oligomers consistent with hexamers o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(70 citation statements)
references
References 47 publications
2
66
1
Order By: Relevance
“…Unlike most AAA ATPases, which exist in oligomeric states without ATP, Kp60 has been reported to be predominantly monomeric and assemble into hexamers in an ATP-and MTdependent manner (Nithianantham et al, 2018;Peng et al, 2013;Roll-Mecak and Vale, 2008;Zehr et al, 2017). However, we found that Kp60AAA shifted from monomeric to hexameric fractions in a concentration-dependent manner, and at high concentrations, both ATP and MT were dispensable for the formation of hexamers ( Figures S1A-S1C).…”
Section: Oligomeric State Of Aaa Atpase Domain Of Human Katanin P60contrasting
confidence: 49%
See 3 more Smart Citations
“…Unlike most AAA ATPases, which exist in oligomeric states without ATP, Kp60 has been reported to be predominantly monomeric and assemble into hexamers in an ATP-and MTdependent manner (Nithianantham et al, 2018;Peng et al, 2013;Roll-Mecak and Vale, 2008;Zehr et al, 2017). However, we found that Kp60AAA shifted from monomeric to hexameric fractions in a concentration-dependent manner, and at high concentrations, both ATP and MT were dispensable for the formation of hexamers ( Figures S1A-S1C).…”
Section: Oligomeric State Of Aaa Atpase Domain Of Human Katanin P60contrasting
confidence: 49%
“…However, we found that Kp60AAA shifted from monomeric to hexameric fractions in a concentration-dependent manner, and at high concentrations, both ATP and MT were dispensable for the formation of hexamers ( Figures S1A-S1C). E/Q mutation in the Walker B motif stabilizes hexamer assembly of MT-severing enzymes (Nithianantham et al, 2018;Peng et al, 2013;Roll-Mecak and Vale, 2008;Zehr et al, 2017). We found that the elution profiles of the EQ mutant (Kp60AAA E309Q ) and the wild-type (Kp60AAA WT ) was similar, showing two peaks corresponding to the sizes of a hexamer and a monomer (Figures 1 and S1A-S1D).…”
Section: Oligomeric State Of Aaa Atpase Domain Of Human Katanin P60mentioning
confidence: 83%
See 2 more Smart Citations
“…The p80 subunit confers targeting and some degree of regulation of the p60 catalytic activity (Hartman et al, 1998;McNally et al, 2014;Wang et al, 2017). Biochemical and structural studies have shown that the p60 and p80 subunits assemble into hexameric ring structures which interact with the C-terminal tails of tubulin and remove tubulin dimers from microtubule sidewalls to promote severing (McNally and Vale, 1993;Hartman and Vale 1999;Zehr et al, 2017, Nithianantham, et al, 2018Vemu, Szczesna, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%